Long-chain polyunsaturated fatty acid status in first-trimester pregnant women (Medical Journal of Indonesia, 2018)
Background: The beneficial effects of long-chain polyunsaturated fatty acid (LCPUFA) on maternal health have been widely investigated in pregnant women. First-trimester supplementation of LCPUFA has been reported to play a role in the inflammatory response, thus reducing a preterm birth and preeclampsia. However, there is a lack of studies investigating the blood concentration of LCPUFA in pregnant women in Indonesia. This study was conducted to evaluate the status of LCPUFA in first-trimester pregnant women in Jakarta, Indonesia.Methods: A descriptive study was conducted using the secondary data of 197 pregnant women in their first trimester who received antenatal care in Budi Kemuliaan Hospital during February 2012 to April 2015. Nutrient intake data were collected through interviews conducted using a semi-quantitative frequency food questionnaire (SQ-FFQ). Total concentrations of linoleic acid (LA), arachidonic acid (AA), alpha-linolenic acid (ALA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) were measured using gas-chromatography/mass spectrometry (GC-MS). Statistical analysis of the data was conducted using SPSS 20.0.Results: Most subjects had deficient blood concentrations of LA (74.1%), AA (85.3%), ALA (76.6%), and DHA (73.1%). The median total concentrations of LA, AA, ALA, EPA, and DHA were as follows: 76.08%, 14.97%, 2.64%, 6.36%, and 1.18%, respectively. The median EPA+DHA level was 7.98%. A total of 38 women (19.3%) were classified as high-risk subjects based on the omega-3 index. No correlation was observed between total DHA+EPA concentration and birth weight (r=0.027, p=0.709). However, a significant difference was detected between the concentrations of LA, AA, and ALA and the maternal body mass index (p<0.05).Conclusion: Most subjects had low intake and blood concentrations of LA, AA, ALA, EPA, and DHA in the first trimester of pregnancy.